An integral approach to sludge handling in a WWTP operated for EBPR aiming phosphorus recovery: Simulation of alternatives, LCA and LCC analyses. (15th May 2020) - Roldán, M.; Bouzas, A.; Seco, A.; Mena, E.; Mayor, Á.; Barat, R.
Abstract: As phosphorus is a non-renewable resource mainly used to produce fertilizers and helps to provide food all over the world, the proper management of its reserves is a global concern since it is expected to become scarcer in the near future. In this work we assessed two different sludge line configurations aiming for P extraction and recovery before anaerobic digestion and compared them with the classical configuration. This study has been performed by simulation with the model BNRM2 integrated in the software package DESASS 7.1. Configuration 1 was based on the production of a PO4 -enriched stream from sludge via elutriation in the primary thickeners, while Configuration 2 was based on the WASSTRIP® process and its PO4 -enriched stream was mechanically obtained with dynamic thickeners. In both alternatives recovery was enhanced by promoting poly-phosphate (poly-P) extraction under anaerobic conditions, for which both configurations were fully evaluated in a full-scale WWTP. Both were also optimized to maximize phosphorus extraction. Their costs and life cycles were also analysed. The novelty of this research lies in the lack of literature about the integral evaluation of pre-anaerobic digestion P recovery from wastewaters. This study included a holistic approach and an optimization study of both alternatives plus their economic and environmental aspects. In Configuration 1, the PO4 –P load in the recovery stream reached 43.1% of the total influent P load and reduced uncontrolled P-precipitation in the sludge line up to 52.9%. In Configuration 2, extraction was 48.2% of the influent P load and it reduced precipitation by up to 60.0%. Despite Configuration 1's lower phosphorus recovery efficiency, it had a 23.0% lower life cycle cost and a 14.2% lower global warming impact per hm 3 of treated influent than Configuration 2. Configuration 1 also reduced the TAEC by 17.6% and global warming impact by 2.0% less than Configuration 0. Graphical abstract: Image 1 Highlights: P extraction before anaerobic digestion enhance P recovery. More than 40% of the influent P load available for recovery as PO4 . Recovery streams with PO4 –P concentrations >100 mgP L −1 . Total extraction of the poly-P before anaerobic digestion. More than 50% of reduction in the uncontrolled P-precipitation.